Development of Student Worksheet Based on Natural Formula as Natural Indicator of Acid Base - Wahyuni, Resti Putri; Hairida, Hairida; Masriani, Masriani (EduChem, 2023)
This research was aimed to produce student worksheet based on natural formula as natural indicator of acid base that is proper to use and to find out the student's response to the products developed. Research Development (RD) was used as from of research which was refer to the 4D model by Thiagarajan, but implementation of the model just limited an 3D section. The subject tested the students of SMA Negeri 1 Sungai Raya Grade XI. Data collection tools were used validation sheets and students response questionnaires on the product developed. The result of the expert validation (expert judgement) obtained that the interpretation is very proper in terms of aspects of content advisability, presentation advisability, linguistic advisability, and graphic advisability with consecutive total scores of 92.5%, 93.8%, 92.6%, and 89.4% respectively. The results of the student's responses in small group trials of 81.45% with very high category and in large group trials of 81.70% in very high category.Keywords: Student Worksheet, Natural Formula, Natural Indicator of Acid Base